Термічні перетворення аморфних акваамінодифосфатів кобальту (II) - нікелю (II) - цинку - Прокопчук, Н.М.; Копілевич, В.А.; Войтенко, Л.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The data of the complex thermal analysis of hydrated cobalt (II) nickel (II) zinc amino diphosphates are presented. The order of the processes occurring at the simultaneous loss of ammonia and water is established. It is shown that, depending on the ratio between metals in the initial substances, the final products of thermolysis are isostructural to either cobalt (II) diphosphate or nickel (II) diphosphate.